HUBUNGAN INISIASI MENYUSU DINI DENGAN KEBERHASILAN ASI EKSKLUSIF DI DESA KEMBARAN WETAN KABUPATEN PURBALINGGA - Arlyana Hikmanti; Etika Dewi Cahyaningrum (Viva Medika, 2014)
Breastfeeding is the best way to provide nutrition for infants aged <6months. Exclusive breastfeeding can begin with the process of early breastfeedinginitiation (IMD). IMD will greatly help boost the immune system of infants aged 1month. Giving late initiation of breastfeeding may increase the risk of death by 24times.Therefore,exclusivebreastfeedingissupportedbytheimplementationof theIMDinwomenafterchildbirth.Themethodusedisanalyticcorrelationbased on primary data taken using a questionnaire to the 71 respondents who hadinfants aged 7-12 months in the village Twinning Wetan Purbalingga. Motherswith infants aged 7-12 months, 52.1% had done IMD, amounting to 62.0% havebeen successful exclusive breastfeeding for 6 months. Based on the results of thestatistical test Chi Square obtain p-value = 1.000 (> 0.1), meaning Ho acceptedand Ha rejected. This shows that there is no correlation between the IMD to thesuccess of exclusive breastfeeding in mothers who had infants aged 7-12 monthsin the village Twinning Wetan Purbalingga. There was no relationship betweenthe IMD to the success of exclusive breastfeeding in mothers who had infantsaged 7-12 months in the village Twinning Wetan Purbalingga. Suggested tomidwives in order to further improve maternal health education on theimportance of exclusive breastfeeding for infants aged 0-6 months although notthrough IMD beforehand. Keywords: IMD, exclusive breastfeeding, mothers with babies 7-12 months